Perubahan Perilaku Pengelolaan Sampah Rumah Tangga di Desa Sialang Rindang, Puskesmas Tambusai, Rokan Hulu - Arti, Eliyah Dwi Setyo; Rahayu, Endang Purnawati; Hanim, Tentri Rapida (Penerbit Goodwood, 2024)
Purpose: This community service is conducted with the aim of increasing community understanding, which will build perceptions and take positive action in managing household waste. Methodology/approach: Community service activities were conducted in Sialang Rindang Village, the working area of the Tambusai Health Center, Rokan Hulu Regency, from November 27 to December 14, 2023. The stages of implementing community service activities began with a pre-test to measure participants' abilities and understanding of household waste management. Subsequently, several interventions were conducted, including outreach, aimed at increasing public understanding and awareness. At the end of the program, a post-test was conducted to determine the level of success in implementing community services. Results/findings: Community service activities begin by deepening the information/evidence base on waste management problems and coordinating community service plans. The results of the field study showed that household waste management only involves the accumulation and burning of waste. Based on the initial information, verification efforts were carried out for further service in the form of counseling/socialization on household waste management for housewives whose activities were focused on the Integrated Healthcare Center. Another service effort is community empowerment through (STBM) cadres to realize community independence in managing household waste. To foster public interest and awareness, a trigger is needed for the community so that waste management efforts can produce products, and waste management assistance is carried out using the 3R method. The waste produced can be managed well and produces products of economic value. Contribution: This research contributes to the literature in the form of attitude change based on an in-depth understanding. This effort allows for attitudes and actions based on continuous understanding. Limitations: The limitations of this service in ongoing monitoring and evaluation are not carried out directly by researchers but by health services.